Conferences on Rural Education School Capacity for Problem Solving. Summaries. - National Inst. of Education (DHEW), Washington, DC.; National Inst. of Education (DHEW), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
Three Rural Education Conferences sponsored during 1977 by the National Institute of Education proposed to find ways to strengthen the capacity of people at the local level to identify and solve their own education problems. The first conference focused on the nature of rural communities and the political, social, economic, and geographic variables which impact upon schools. Participants agreed that identification of problems and efforts to solve them should be initiated by those involved in and affected by the local education program, not by outside experts. The second conference explored the participants' experiences with a variety of programs designed to improve education in rural settings. Capacity building strategies derived from experiences related in the conference included: collaborative problem solving; community organization; regional information exchange and referral service; inter-agency coordination; associations of users; networking; and leadership development. School administrators and education decision makers added perspectives on rural school improvement in the third conference, identified critical elements that should be part of any strategy (community involvement, leadership development, and networking), and asserted that because rural settings are so varied, it may be more difficult to generalize across rural settings than across urban ones. Lists of participants in each conference are included. (NEC)
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Involvement; Educational Change; Educational Improvement; Educational Strategies; Elementary Secondary Education; Leadership; Local Issues; Problem Solving; Rural Areas; Rural Education; Rural Schools; School Community Relationship; Collected Works, Proceedings